Sobre as Identidades no Jornal de Umbanda: Órgão Noticioso e Doutrinário da União Espiritista de Umbanda (1949-1960) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
This study aims to address some of the tensions present in the narratives of the "Jornal de Umbanda: Orgão Noticioso e Doutrinário da União Espiritista de Umbanda," which was active in Rio de Janeiro from 1949 to 1960. During this period, the writers expressed their opinions on the Umbanda religion in open debate with readers from across Brazil. Analyzing materials from these periodicals and the report of the 1st Congress of Umbanda Spiritualism in Brazil in 1941, which significantly influenced debates in the journal, the articles were examined with a focus on identity criteria. Narrative collection techniques were employed within the newspapers, available online through the National Hemeroteca, aligning with a consistent theoretical and methodological framework. Some of the theoretical and methodological foundations used in this work include Tânia de Luca, Artur Cesar Isaia, Flavia Pinto, Luiz Antonio Simas, Jessé Souza, Peter Berger, Peter Burke, Pierre Bourdieu, Stuart Hall, among others. Overall, the research revolves around the newspaper's representation of a quest for the strengthening of an Umbandist identity consistent with the context at hand, legitimized by an institution called the União Espiritista de Umbanda do Brasil (UEUB), which served as the spokesperson for all Umbandists accepting such a proposal. The analysis of the newspaper articles and the report involves interpreting political, social, racial, cultural, and other perspectives that represented the primary concerns of Umbandists affiliated with the UEUB.
Keywords: Umbanda; Umbandistas; Jornal; Identidade; Umbanda; Umbandists; Journal; Identity; CNPQ::CIENCIAS HUMANAS::HISTORIA